The Assessment of the Quality of Water from Regional Drinking Water Company Giri Menang as a Source of Community drinking water in the City of Mataram - Baiq Desi Hariani; Agil Al Idrus; Khairuddin Khairuddin (Jurnal Biologi Tropis, 2021)
Drinking water is one of the most essential human needs. The purpose of this study was to investigate the status of the water quality of PDAM Giri Menang as a source of drinking water for people in Mataram area based on physical, chemical, and microbiological parameters. Determination of sample points was done by random sampling method while the samples were collected by using composite sample method. The results of analysis of physical parameters (odor, taste, turbidity, temperature, color), chemical parameters (dissolved oxygen, iron (Fe), pH, hardness, manganese (Mn), chloride (Cl-), ammonia (NH4), cadmium (Cd) ), and the microbiological parameters including the presence of E.coli bacteria and total Coliform in the five PDAM water samples generally meet the quality of drinking water since the value of each parameter was below the maksimum value set by Permenkes RI No. 492/2010 concerning requirements quality of drinking water. The conclusion from the research results shows that the status of water quality PDAM Giri Menang as a source of drinking water for people in Mataram area is very good according to the mandatory parameters, namely physics, chemistry, and microbiology that are in accordance with the Republic of Indonesia Minister of Health Regulation No. 492/2010 regarding the requirements for the quality of drinking water. The results of this study can be used as a reference for further research with more samples and parameters, especially in the city of Mataram and West Lombok.